What do we do now that the long-acting growth hormone is here? - Miller, Bradley S. (Frontiers in Endocrinology, 2022)
In standard 52 week phase III clinical trials, once weekly lonapegsomatropin, somatrogon and somapacitan have been found to yield non-inferior height velocities and similar safety profiles to daily GH (DGH) in children with pediatric growth hormone deficiency (PGHD). Lonapegsomatropin, a long-acting GH therapy (LAGH), was approved by the United States Food and Drug Administration (FDA) in August 2021 for the treatment of PGHD and has also been approved in other regions of the world. Somatrogon was approved for the treatment of PGHD beginning in some regions beginning in late 2021. Somapacitan was approved by the FDA for the treatment of Adult GHD in August 2020. The phase III clinical trial of somapacitan for the treatment of PGHD has been completed and demonstrated non-inferiority of somapacitan to DGH. New LAGH products may improve patient adherence, quality of life and clinical outcomes, particularly in patients with poor adherence to daily GH injections in the future. With the availability of new LAGH products, clinicians will need to identify the best candidates for LAGH therapy and understand how to monitor and adjust therapy. Long-term surveillance studies are needed to demonstrate adherence, efficacy, cost-effectiveness and safety of LAGH preparations and to understand how the non-physiological pharmacokinetic and pharmacodynamic profiles following administration of each LAGH product relate to short- and long-term safety and efficacy of LAGH therapy.